Antileishmanial, Toxicity, and Phytochemical Evaluation of Medicinal Plants Collected from Pakistan. (19th May 2014) - Shah, Naseer Ali; Khan, Muhammad Rashid; Nadhman, Akhtar
Abstract : Leishmaniasis is an important parasitic problem and is in focus for development of new drugs all over the world. Objective of the present study was to evaluate phytochemical, toxicity, and antileishmanial potential of Jurinea dolomiaea, Asparagus gracilis, Sida cordata, and Stellaria media collected from different areas of Pakistan. Dry powder of plants was extracted with crude methanol and fractionated with n -hexane, chloroform, ethyl acetate, n -butanol, and water solvents in escalating polarity order. Qualitative phytochemical analysis of different class of compounds, that is, alkaloids, saponins, terpenoids, anthraquinones, cardiac glycosides, coumarins, phlobatannins, flavonoids, phenolics, and tannins, was tested. Its appearance was observed varying with polarity of solvent used for fractionation. Antileishmanial activity was performed against Leishmania tropica KWH23 promastigote. Potent antileishmanial activity was observed for J. dolomiaea methanol extract (I C 50 = 10.9 ± 1.1   μ g/mL) in comparison to other plant extracts. However, J. dolomiaea "ethyl acetate fraction" was more active (IC 50 = 5.3 ± 0.2   μ g/mL) against Leishmania tropica KWH23 among all plant fractions as well as standard Glucantime drug (6.0 ± 0.1   μ g/mL). All the plants extract and its derived fraction exhibited toxicity in safety range (L C 50   > 100 ) in brine shrimp toxicity evaluation assay.